Doing Women's History in Public: A Handbook for Interpretation at Museums and Historic Sites - Huyck, Heather (Rowman & Littlefield Publishers, 2020)
A complete guide to interpreting women’s history. Women’s history is everywhere, not only in historic house museums named for women but also in homes named for famous men, museums of every conceivable kind, forts and battlefields, even ships, mines, and in buckets. Women’s history while present at every museum and historic site remains less fully interpreted in spite of decades of vibrant and expansive scholarship. Doing Women’s History in Public: A Handbook for Interpretation at Museums and Historic Sites connects that scholarship with the tangible resources and the sensuality that form museums and historic sites-- the objects, architecture and landscapes-- in ways that encourage visitor fascination and understanding and center interpretation on the women active in them. With numerous examples that focus on all women and girls, it appropriately includes everyone, for women intersect with every other human group. This book provides arguments, sources (written, oral, and visual), and tools for finding women’s history, preserving it, and interpreting it with the public. It uses the framework of Significance (importance), Knowledge Base (research in primary, secondary, and tertiary sources), and Tangible Resources (the preserved physical embodiment of history in objects, architecture, and landscapes). Discusses traditional and technology-assisted interpretation and provides Tools to implement Doing Women’s History in Public. Using a hospitality model, museums and historic sites are the locales where we assemble, learn from each other, and take our insights into a more gender-shared future.